Gambaran social self-efficacy, self-disclosure, dan status pertemanan pada mahasiswa baru - Kartikarini, Rosa Virginia; Purwanti, Margaretha (Faculty of Psychology Universitas 17 Agustus 1945 Surabaya, 2022)
Abstract Due to the social restrictions during the covid-19 pandemic, making friends has become a challenge for students studying from home. This study aims to describe and examine the correlation between self-disclosure, social self-efficacy, and friendship status. Participants (N = 221) were freshman students of the 2021 cohort from Universities in Jabodetabek. Data was collected with convenience sampling and analysed using descriptive analysis and correlation. The measurement instrument used in this study was Self-Efficacy Scale in Personal Relationship (α=0.927), the Revised Self-Disclosure Scale (α=0.801), and the friendship status category. Results indicate that social self-efficacy and self-disclosure were fairly high among freshman students and the majority of friendship status was in the first initiation step. One-Way ANOVA showed that there is a significant difference in social self-efficacy and self-disclosure between friendship status. Spearman Correlation showed that there is a significant positive correlation between social self-efficacy, self-disclosure, and friendship status. Keywords: freshman college students; friendship status; self-disclosure; social self-efficacy Abstrak Pandemi Covid-19 membuat pembentukan pertemanan semakin menantang karena interaksi mahasiswa mayoritas dilaksanakan secara daring. Penelitian ini bertujuan untuk melihat gambaran social self-efficacy (SSE), self-disclosure, dan status pertemanan dalam membangun pertemanan pada mahasiswa baru angkatan 2021 di Jabodetabek. Penelitian ini merupakan penelitian kuantitatif komparasi dan korelasi. Instrumen penelitian menggunakan alat ukur Self-Efficacy Scale in Personal Relationship (α=0.927), Revised Self-Disclosure Scale (α=0.801), dan Kategori Status Pertemanan yang telah melalui proses adaptasi dengan expert judgement dan face validity. Responden terdiri dari 221 mahasiswa baru dari universitas di Jabodetabek yang dipilih dengan teknik convenience sampling. Berdasarkan analisis statistik deskriptif ditemukan bahwa SSE dan self-disclosure pada kategori cukup tinggi, dan status pertemanan berada pada tahap pertama yaitu inisiasi. Uji One-Way ANOVA menunjukkan terdapat perbedaan signifikan pada SSE dan self-disclosure berdasarkan status pertemanan. Uji Korelasi Spearman ditemukan hubungan positif yang signifikan antara SSE dengan self-disclosure, SSE dengan status pertemanan, dan self-disclosure dengan status pertemanan. Keywords: mahasiswa baru; self-disclosure; social self-efficacy; status pertemanan